Targeted stabilization of Munc18‐1 function via pharmacological chaperones - Debra Abramov; Noah Guy Lewis Guiberson; Andrew Daab; Yoonmi Na; Gregory A Petsko; Manu Sharma; Jacqueline Burré (EMBO Molecular Medicine, 2020)
Abstract Heterozygous de novo mutations in the neuronal protein Munc18‐1 cause syndromic neurological symptoms, including severe epilepsy, intellectual disability, developmental delay, ataxia, and tremor. No disease‐modifying therapy exists to treat these disorders, and while chemical chaperones have been shown to alleviate neuronal dysfunction caused by missense mutations in Munc18‐1, their required high concentrations and potential toxicity necessitate a Munc18‐1‐targeted therapy. Munc18‐1 is essential for neurotransmitter release, and mutations in Munc18‐1 have been shown to cause neuronal dysfunction via aggregation and co‐aggregation of the wild‐type protein, reducing functional Munc18‐1 levels well below hemizygous levels. Here, we identify two pharmacological chaperones via structure‐based drug design, that bind to wild‐type and mutant Munc18‐1, and revert Munc18‐1 aggregation and neuronal dysfunction in vitro and in vivo, providing the first targeted treatment strategy for these severe pediatric encephalopathies.